2019
DOI: 10.1111/jmi.12798
|View full text |Cite
|
Sign up to set email alerts
|

X‐ray microfocus computed tomography: a powerful tool for structural and functional characterisation of 3D printed dosage forms

Abstract: Summary One of the most promising advances in modern pharmaceutical technology is the introduction of three‐dimensional (3D) printing technology for the fabrication of drug products. 3D printed dosage forms have the potential to revolutionise pharmacotherapy as streamlined production of structurally complex formulations with optimal drug releasing properties is now made possible. 3D printed formulations are derived as part of a process where a ‘print‐head’ deposits, or sinters material under computer control t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…To check the accuracy of the printing, as well as to determine the porosity of the printed tablets, µCT measurements are often used [ 102 , 122 ]. The visualization of the internal structure of dosage forms reveals the structural quality, how well the layers adhere to each other, and how well the geometry matches the desired design without destruction of the tablet [ 123 , 124 ]. In a study by Alhijjaj et al, it was shown that the printing speed, printing temperature, build plate leveling and polymer viscosity (melt flow index) have a high influence on the precision of the print, weight of the object and print reproducibility [ 125 ].…”
Section: D Printed Dosage Forms For Pediatric Usementioning
confidence: 99%
“…To check the accuracy of the printing, as well as to determine the porosity of the printed tablets, µCT measurements are often used [ 102 , 122 ]. The visualization of the internal structure of dosage forms reveals the structural quality, how well the layers adhere to each other, and how well the geometry matches the desired design without destruction of the tablet [ 123 , 124 ]. In a study by Alhijjaj et al, it was shown that the printing speed, printing temperature, build plate leveling and polymer viscosity (melt flow index) have a high influence on the precision of the print, weight of the object and print reproducibility [ 125 ].…”
Section: D Printed Dosage Forms For Pediatric Usementioning
confidence: 99%
“…In this case, the microstructure is addressed by the density, pore size distribution, and the distribution of the components of a formulation within the tablet framework. Different studies show the suitability of the non-destructive X-ray microtomography (XMT) for the 3D characterization of particulate structures and especially of solid dosage forms ( Feinauer et al, 2015 ; Strege et al, 2014 ; Leißner et al, 2020 ; Busignies et al, 2006 ; Sinka et al, 2004 ; Landis and Keane, 2010 ; Gioumouxouzis et al, 2020 ; Hancock and Mullarney, 2005 ; Maire and Withers, 2014 ). First studies of the suitability of XMT for the characterization of the microstructure of compacted materials were performed by Lannutti ( Lannutti, 1997 ) and by Burch ( Burch, 2002 ).…”
Section: Introductionmentioning
confidence: 99%
“…Only Gioumouxouzis et al have utilized X-ray microtomography (XmCT) to study FDMprinted tablets during incubation in a dissolution medium. 11 The functional property of pharmaceutical matrix systems, including 3D printed formulations, is drug release, which is related to mass transport phenomena, i.e., dissolution medium ingress and active substance transport outside the system via a combination of various phenomena. Additionally, it is supposed that formulations presented by Krkobabic et al, 12,13 based on polyethylene glycol diacrylate (PEGDA) and low molecular weight polyethylene glycol (PEG), will involve two mobile phase transport during the dissolution process, i.e., water (dissolution medium entering the matrix) and PEG (incorporated in the matrix during manufacturing as an excipient).…”
Section: Introductionmentioning
confidence: 99%
“…Typically, two simple gravimetric techniques, water uptake (denoted as swelling) and erosion assessment, are applied to analyze water transport and matrix behavior, similar to traditional dosage forms. Only Gioumouxouzis et al have utilized X-ray microtomography (XmCT) to study FDM-printed tablets during incubation in a dissolution medium …”
Section: Introductionmentioning
confidence: 99%